Binocular coordination during smooth pursuit in dyslexia: a multiple case study - Qing Yang; Marine Vernet; Maria-Pia Bucci; Zoe Kapoula (Bern Open Publishing, 2010)
Smooth pursuit (SP) was explored in dyslexics and non-dyslexics. Dyslexic children show similar gain of SP, and number and amplitude of catch-up saccades (CUS) as non-dyslexic children. The quality of binocular coordination is good for both groups; the only significant exception is for pursuit to the right for both smooth phase and CUS; dyslexics show higher disconjugacy. Decrement of binocular control during rightward pursuit only could reflect immaturity of oculomotor learning mechanisms needed to optimize binocular coordination for all directions. Yet, these observations need to be confirmed in a larger population including older children and compared with other populations, e.g. with right-to-left reading.